Highly time-resolved chemical characterization of atmospheric fine particles during 2010 Shanghai World Expo - X.-F. Huang (Atmospheric Chemistry and Physics, 2012)
Shanghai, with a population of over 20 million, is the largest mega-city in China. Rapidly increasing industrial and metropolitan emissions have deteriorated its air quality in the past decades, with fine particle pollution as one of the major issues. However, systematic characterization of atmospheric fine particles with advanced measurement techniques has been very scarce in Shanghai. During 2010 Shanghai World Expo, we deployed a high-resolution time-of-flight aerosol mass spectrometer (HR-ToF-AMS) and a single particle soot photometer (SP2) in urban Shanghai between 15 May and 10 June 2010 to measure fine particles with a high time resolution. The 4-min resolution PM1 mass concentration ranged from 5.5 to 155 μg m−3, with an average of 29.2 μg m−3. On average, sulfate and organic matter (OM) were the most abundant PM1 components, accounting for 33.3 and 28.7% of the total mass, respectively, while the fraction of nitrate showed an increasing trend with the increasing PM1 loading, indicating the photochemical nature of high fine particle pollution in Shanghai. Taking advantage of HR-ToF-AMS and SP2, OM was found to have an average OM/OC ratio (organic matter mass/organic carbon mass) of 1.55 and black carbon (BC) had an average number fraction of internally mixed BC of 41.2%. Positive matrix factorization (PMF) analysis on the high resolution organic mass spectral dataset identified a hydrocarbon-like (HOA), a semi-volatile oxygenated (SV-OOA), and a low-volatility oxygenated (LV-OOA) organic aerosol component, which on average accounted for 24.0, 46.8, and 29.2% of the total organic mass, respectively. The diurnal patterns of them with interesting time delay possibly implied a photochemical oxidizing process from HOA (and/or its concurrently emitted gaseous organic pollutants) to SV-OOA to LV-OOA. Back trajectory analysis indicated that the northwesterly continental air mass represented the most severe pollutant regional transport condition with the highest nitrate and SV-OOA fractions. In addition, the results in Shanghai were compared with similar measurements performed recently in other mega-cities in the world.